2019
DOI: 10.1002/pamm.201900144
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of continuously differentiable Galerkin time discretizations for the wave equation

Abstract: In this work we compare numerically two families of space-time finite element approximation schemes for wave equations. Continuously differentiable in time discrete solutions are provided by the schemes. The first family of schemes is based on a computationally cheap post-processing of the continuous in space and time finite element approximation of the wave equation. The second family combines the variational approximation in time by finite element techniques with the concepts of collocation methods. Both fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The conceptual basis of the families of approximations to the wave equation is the establishment of a connection between the Galerkin method for the time discretization and the classical collocation methods, with the perspective of achieving the accuracy of the former with reduced computational costs provided by the latter in terms of less complex algebraic systems. Further numerical studies for the wave equation can be found in [11,5]. For the application of the Galerkin-collocation to mathematical models of fluid flow and systems of ordinary differential equations we refer to [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual basis of the families of approximations to the wave equation is the establishment of a connection between the Galerkin method for the time discretization and the classical collocation methods, with the perspective of achieving the accuracy of the former with reduced computational costs provided by the latter in terms of less complex algebraic systems. Further numerical studies for the wave equation can be found in [11,5]. For the application of the Galerkin-collocation to mathematical models of fluid flow and systems of ordinary differential equations we refer to [4,15,16].…”
Section: Introductionmentioning
confidence: 99%